Charge migration engineered by localisation: electron-nuclear dynamics in polyenes and glycine. (18th October 2018) - Polyak, Iakov; Jenkins, Andrew J.; Vacher, Morgane; Bouduban, Marine E. F.; Bearpark, Michael J.; Robb, Michael A.
ABSTRACT: We demonstrate that charge migration can be 'engineered' in arbitrary molecular systems if a single localised orbital – that diabatically follows nuclear displacements – is ionised. Specifically, we describe the use of natural bonding orbitals in Complete Active Space Configuration Interaction (CASCI) calculations to form cationic states with localised charge, providing consistently well-defined initial conditions across a zero point energy vibrational ensemble of molecular geometries. In Ehrenfest dynamics simulations following localised ionisation of -electrons in model polyenes (hexatriene and decapentaene) and -electrons in glycine, oscillatory charge migration can be observed for several femtoseconds before dephasing. Including nuclear motion leads to slower dephasing compared to fixed-geometry electron-only dynamics results. For future work, we discuss the possibility of designing laser pulses that would lead to charge migration that is experimentally observable, based on the proposed diabatic orbital approach. GRAPHICAL ABSTRACT: